Quality Assurance for Postgraduate Programs: Design of a Model Applied on a University in Chile - Careaga Butter, Marcelo; Meyer Aguilera, Eduardo; Badilla Quintana, María Graciela; Jiménez Pérez, Laura; Sepúlveda Valenzuela, Eileen (International Review of Research in Open and Distributed Learning, 2017)
The quality of Education in Chile is a controversial topic that has been in the public debate in the last several years. To ensure quality in graduate programs, accreditation is compulsory. The current article presents a model to improve the process of self-regulation. The main objective was to design a Model of Quality Assurance for Postgraduate Programs in order to constitute a theoretical, mathematical, and informatics reference that would optimize the processes of self-regulation, self-evaluation, and accreditation of master and doctorate programs from the Universidad Católica de la Santísima Concepción, Chile. This descriptive research is based on a mixed methods approach. The proposal was intended through theoretical and empirical references related to the accreditation systems. The analysis process was conducted with key informants, and the informatics instrument was created and validated through expert judgment. After the analysis, the model was optimized considering the expert’s suggestions. As a result of the optimization process, a matrix of eight dimensions was obtained and it is available online in order to be used by the heads of postgraduate programs. Finally, a model with four main stages was achieved in order to install a self-regulation and a self-evaluated culture that leads to accreditation as evidence of the quality of postgraduate programs.